2007
DOI: 10.1136/bjo.2007.116947
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of autotaxin predicts survival in uveal melanoma

Abstract: Aim: In an effort to identify patients with uveal melanoma at high risk of metastasis, the authors undertook correlation of gene expression profiles with histopathology data and tumour-related mortality. Methods: The RNA was isolated from 27 samples of uveal melanoma from patients who had consented to undergo enucleation, and transcripts profiled using a cDNA array comprised of sequence-verified cDNA clones representing approximately 4000 genes implicated in cancer development. Two multivariate data mining tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…It was shown that ATX is differentially expressed in non-cancerous (low) and cancerous (high) tissues, suggesting that ATX could be a marker of the process [105]. It has been suggested that serum ATX might be used as a marker in follicular lymphoma [61], uveal melanoma [106] or chronic hepatitis C [52,107].…”
Section: Autotaxin and Physio-pathologymentioning
confidence: 99%
“…It was shown that ATX is differentially expressed in non-cancerous (low) and cancerous (high) tissues, suggesting that ATX could be a marker of the process [105]. It has been suggested that serum ATX might be used as a marker in follicular lymphoma [61], uveal melanoma [106] or chronic hepatitis C [52,107].…”
Section: Autotaxin and Physio-pathologymentioning
confidence: 99%
“…High-throughput technologies, including cDNA microarrays and aCGH array analysis, have been the focus of many recent papers that have identiWed various "molecular-genetic signatures" for this particular neoplasm Zuidervaart et al 2003;Onken et al 2004;Marshall et al 2007;Meir et al 2007;Singh et al 2007). While these papers have presented very consistent data that identify signiWcant chromosomal aberrations in chromosome 3, 6 and 8 (Aalto et al 2001;White et al 2006;Onken et al 2007;Mensink et al 2008;van Gils et al 2008), the tissue used for these transcriptional studies were mostly fresh frozen and are more diYcult to acquire due to the fact that enucleation is no longer the primary treatment for UM.…”
Section: Introductionmentioning
confidence: 99%
“…When two gene signatures of 25 uveal melanomas were compared with respect to a 92-month survival probability, gene expression profiling was found to be associated with survival [25]. Singh et al [26] studied gene expression data of 27 uveal melanoma samples and showed that a poor patient survival was related to the expression of genes encoding the histocompatibility complex class I and class II, as well as other immune response genes (e.g. the nuclear factor of activated T cells, macrophage stimulating pseudogene 9).…”
Section: Genome-wide Microarray Analysismentioning
confidence: 99%